Epidemiology and Clinical Characteristics of Dermatophytosis in The Southern Region of Bangladesh: A Cross-sectional Study (Mediscope, 2025)
Background and objective: The dermatophytoses constitute a group of superficial fungal infections of keratinized tissues, namely, the epidermis, hair, and nails. The distribution and frequency of dermatophytosis vary according to the geographic region studied. The present study was undertaken to assess the clinical and epidemiological profile of dermatophytic infections in the Southern region of Bangladesh.Methods: A cross-sectional study was conducted from July 2024 to December 2024 in the outpatient department (OPD) of skin and venereal diseases (Skin & VD) at Gazi Medical College Hospital (GMCH), Khulna, and three private practice chambers in Khulna, Narail and Gopalganj districts. A total of 370 patients of all age groups and both genders were included in the study. Data regarding demographics and clinical types were recorded and analyzed.Results: Among the total 370 dermatophytosis cases, there were 174 males and 196 females. The majority of the respondents belonged to the age groups of 16-30 years and 31-40 years, each consisting of 121 (32.7%) patients. A positive family history was found in 70.5% of cases. Tinea corporis (28.6%) was the prominent clinical type of single-site infection. Among the multiple-site infection cases, T. corporis with T. cruris was the most frequent (85.6%).Conclusion: This study provides key information regarding the epidemiological pattern of dermatophytosis. The concerned sectors need to build awareness in the population regarding dermatophytosis so as to minimize the disease burden in society.Mediscope 2025;12(2): 49-53